Pengelolaan Limbah Farmasi Rumah Sakit Berbasis Green Hospital: Tinjauan Literatur terhadap Kebijakan dan Praktik Berkelanjutan - Rahmi, Sherly Firsta; Kasmiati, Neng; Amalia, Rosi; Dewi, Nur Husna; Yorismanto, Yorismanto; Hartono, Budi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing intensity of healthcare services in hospitals has led to a growing volume of pharmaceutical waste that poses potential risks to human health and the environment. Various reports indicate that a proportion of hospitals have not yet effectively managed pharmaceutical waste, thereby increasing the risk of environmental contamination and adverse impacts on the health of surrounding communities. Pharmaceutical waste generated by hospitals, including expired medicines, unused drugs, and pharmaceutical packaging, requires proper management to prevent environmental pollution. The green hospital concept has emerged as a sustainable approach that emphasizes environmentally friendly hospital management, including pharmaceutical waste management. This study aims to review policies, impacts, and strategies for hospital pharmaceutical waste management based on the green hospital approach through findings from previous studies. The research method employed is a literature review by analyzing relevant national and international scientific articles. The results of the review indicate that ineffective pharmaceutical waste management can lead to environmental contamination and public health risks, while the implementation of green hospital strategies—such as waste prevention, source segregation, and the strengthening of internal policies—can improve the effectiveness of pharmaceutical waste management. In conclusion, pharmaceutical waste management based on the green hospital concept represents an important strategy for supporting environmental sustainability in hospitals and protecting public health.